Studi Komparatif Pengaruh Model kontekstual terhadap Kemampuan Pemecahan Masalah Persamaan Linier Satu Variabel Siswa Kelas IX SMP - Linda Permata Sari; Sabrinatur Rasyidah; Rizal Kurniawan; Nur Wiji Sholikin (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to examine the effect of the contextual learning model on students’ learning outcomes in the topic of Linear Equations in One Variable (LEOV). The research employed a quantitative approach with a pre-experimental design using a one-group pretest–post-test model. The participants consisted of 30 students who were given a pretest before the implementation of contextual learning and a post-test after the learning process. The research instrument was a learning achievement test developed based on the indicators of LEOV competencies. Data were analysed using a paired samples t-test and N-Gain analysis to determine the significance and effectiveness of the learning model. The results showed that the mean pretest score of students was 55.00, which increased to 84.00 in the post-test. The paired samples t-test indicated a significance value of 0.000 < 0.05, revealing a significant difference between students’ learning outcomes before and after the implementation of contextual learning. Furthermore, the N-Gain value of 0.64 was classified as moderate. These findings indicate that the contextual learning model has a significant and fairly effective impact on improving students’ learning outcomes in Linear Equations in One Variable, although the improvement was not evenly distributed among all students.